Cut-off for the Life-Space Assessment in persons with cognitive impairment - Ullrich, Phoebe; Werner, Christian; Eckert, Tobias; Bongartz, Martin; Kiss, Rainer; Feißt, Manuel; Delbaere, Kim; Bauer, Jürgen M.; Hauer, Klaus (Aging clinical and experimental research, 2019)
Background: A version of the Life-Space Assessment in persons with cognitive impairment (LSA-CI) has recently been developed. Aims: To establish a cut-off value for the newly developed Life-Space Assessment in persons with cognitive impairment (LSA-CI). Methods: In a cross-sectional study including 118 multimorbid, older persons with cognitive impairment, life-space mobility (LSM) was documented by the LSA-CI. The analysis was rationalized by Global Positioning System (GPS)-based measures of spatial distance from home. A receiver-operating characteristic (ROC) curve was created and the cut-off point for the LSA-CI was identified with the Youden’s Index. Results: ROC curve analysis indicated a critical value of 26.75 (within a range of 0-90) to differentiate between low and high LSM with a sensitivity of 78.1% and specificity of 84.2%. Discussion: Diagnostic interpretation of the ROC curves revealed that low and high LSM groups can be differentiated with the proposed cut-off. Conclusions: The proposed LSA-CI cut-off score can be recommended to tailor clinical interventions and evaluate change over time.